2014
DOI: 10.1093/treephys/tpu032
|View full text |Cite
|
Sign up to set email alerts
|

Foliar uptake, carbon fluxes and water status are affected by the timing of daily fog in saplings from a threatened cloud forest

Abstract: In cloud forests, foliar uptake (FU) of water has been reported for numerous species, possibly acting to relieve daily water and carbon stress. While the prevalence of FU seems common, how daily variation in fog timing may affect this process has not been studied. We examined the quantity of FU, water potentials, gas exchange and abiotic variation at the beginning and end of a 9-day exposure to fog in a glasshouse setting. Saplings of Abies fraseri (Pursh) Poir. and Picea rubens Sarg. were exposed to morning (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 36 publications
5
52
0
Order By: Relevance
“…Both Eller et al () and Cassana et al (2016) find evidence that water from FWU was transported to soil in seedlings of a tropical evergreen ( Drimys brasiliensis ) and a southern hemisphere conifer ( Araucaria angustifolia ) in Brazil. However, Limm et al () and Berry, White, and Smith () conducted similar studies and did not find any signal of FWU water in the soil in seedlings from temperate California Redwoods (10 herbaceous and tree species) and in Appalachian montane conifer forests (canopy conifers), respectively. Notably, recent research has demonstrated that stable isotopes of water alone cannot be used as tracers to establish the net uptake of water by FWU, due to the possibility of bidirectional exchange of water isotopes between the leaf and the atmosphere (Goldsmith, Lehmann, Cernusak, Arend, & Siegwolf, ).…”
Section: Pathways Of Water Movementmentioning
confidence: 85%
“…Both Eller et al () and Cassana et al (2016) find evidence that water from FWU was transported to soil in seedlings of a tropical evergreen ( Drimys brasiliensis ) and a southern hemisphere conifer ( Araucaria angustifolia ) in Brazil. However, Limm et al () and Berry, White, and Smith () conducted similar studies and did not find any signal of FWU water in the soil in seedlings from temperate California Redwoods (10 herbaceous and tree species) and in Appalachian montane conifer forests (canopy conifers), respectively. Notably, recent research has demonstrated that stable isotopes of water alone cannot be used as tracers to establish the net uptake of water by FWU, due to the possibility of bidirectional exchange of water isotopes between the leaf and the atmosphere (Goldsmith, Lehmann, Cernusak, Arend, & Siegwolf, ).…”
Section: Pathways Of Water Movementmentioning
confidence: 85%
“…, top and middle panels; Simonin et al ., ). Similar results have been observed in tropical and temperate montane cloud forest trees (Eller et al ., ; Berry et al ., ). Moreover, although there is now strong evidence that photosynthesis can be sustained by transient leaf wetting events, there is also emerging evidence suggesting that the immediate effects of leaf wetting on photosynthesis may vary considerably among species.…”
Section: The Real and Potential Benefits Of Leaf Wettingmentioning
confidence: 97%
“…The occurrence of water entering leaves directly from the atmosphere has two major implications, the first being that it increases the total amount of water available to the plant, and by extension, the amount of carbon assimilated (Berry, White, & Smith, 2014;Oliveira, Eller, Bittencourt, & Mulligan, 2014). The second implication is that water entering at the top of the system can effectively act independently of the cohesion-tension theory-that is, it enables water pressure in the canopy xylem to be above the theoretical maximum pressure based on water supply from the soil (Goldsmith, 2013)-and hypothetically even achieve positive pressures.…”
Section: Introductionmentioning
confidence: 99%